Peningkatan Ekonomi Pesantren Modern Al-Falah Abu Lam-U Melalui Koperasi Pontren - Amanatillah, Dara; Hermawan, Yudi; Nizam, Ahmad (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2023)
The co-operation of the hostel is one of the Bodies of Owned by Pesantren (BUMP) that serves to meet the needs of the sanctuary. The aim of this study is (1) to know how the role of Islamic cooperation (kopontren) in increasing the economic income in the Modern Al Falah Abu Lam U (2) to know the measures of co-operation of the establishment in improving the economic revenue of the Modern al Falah Abu Lam U. After the author doing the observations with a total of 567 santri are expected to help the economic income of the party through the presence of a co-trend, but this is still not optimal. To this goal, a qualitative assessment approach is used with the type of field research. In this writing, researchers use data collection techniques, is interviews, observations and documentation. The results of this study showed that: (1) the role of the cooperative in increasing the economic income of the participant has increased marked by the presence of monthly and annual financial reports, but still has not maximized the results deposited on the part of the representative, both material and non-material. (2) Steps in improving co-trend strategies use SWOT analysis to identify the strengths, opportunities and threats in co-traded development